2011
DOI: 10.1002/eco.197
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects on transpiration, canopy conductance, stomatal sensitivity to vapour pressure deficit, and cavitation resistance in loblolly pine

Abstract: Physiological uniformity and genetic effects on canopy-level gas-exchange and hydraulic function could impact loblolly pine (Pinus taeda L.) plantation sustainability and ecosystem dynamics under projected changes in climate. Over a 1-year period, we examined genetic effects on mean and maximum mid-day canopy conductance (G s , G smax ) and transpiration (E, max-E) within a juvenile loblolly pine plantation composed of 'genotypes' (e.g. different genetic entries) from each of the three different genetic groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 80 publications
0
15
1
4
Order By: Relevance
“…This effect was even more pronounced in the throughfall reduction with fertilizer application treatment, which decreased G Cref from 171.9 to 119.0 mmol·m −2 ·s −1 . The contrast between the results of this study and those of Bartkowiak et al [50] may be due to differences in site conditions and/or differences in genetics, as the genetics of loblolly pine has been shown to affect G Cref and δ [19,20]. For example, Gonzalez-Benecke and Martin [19] found that irrigation increased G Cref and δ in a South Carolina loblolly pine seed source while a Florida seed source was unaffected.…”
Section: Canopy Conductancecontrasting
confidence: 85%
“…This effect was even more pronounced in the throughfall reduction with fertilizer application treatment, which decreased G Cref from 171.9 to 119.0 mmol·m −2 ·s −1 . The contrast between the results of this study and those of Bartkowiak et al [50] may be due to differences in site conditions and/or differences in genetics, as the genetics of loblolly pine has been shown to affect G Cref and δ [19,20]. For example, Gonzalez-Benecke and Martin [19] found that irrigation increased G Cref and δ in a South Carolina loblolly pine seed source while a Florida seed source was unaffected.…”
Section: Canopy Conductancecontrasting
confidence: 85%
“…Few of these molecular studies have focused on xylem cavitation, probably because of the time consuming phenotyping involved (but see Plavcova et al () for an example where it was performed). Some have evaluated the effect of ploidy levels on hydraulic traits including cavitation resistance (Maherali et al ; Hao et al ), others aquaporins expression and their effect on conductance or refilling (e.g., Hacke et al ; Secchi and Zwieniecki ), and several the relationships between population genetic diversity, cavitation resistance and the plasticity of this trait (Aspinwall et al ; Corcuera et al ; Lamy et al , ; Schreiber et al , ; Wortemann et al ; López et al , ). Most of the latter studies found limited genetic effect on hydraulic trait variations which were largely due to phenotypic plasticity, but in Pinus canariensis and Artemisia tridentata support for local adaptation of traits related to hydraulic safety and survival was also found (Kolb and Sperry , ; López et al , ).…”
Section: Molecular Biology Of Xylem Functionmentioning
confidence: 99%
“…Those examined variables in this special issue include genetic variants of tree species (e.g. loblolly pine by Aspinwall et al, 2011), structural and physiological control , elevated carbon dioxide (Warren et al, 2011) and extreme climate events (e.g. spring drought by Dong et al, 2011).…”
Section: The Nature and Scope Of The Special Issuementioning
confidence: 99%